The role of Rhipicephalus (Boophilus) decoloratus, Rhipicephalus appendiculatus and Amblyomma hebraeum in the transmission of lumpy skin disease virus - Venter, Estelle Hildegard (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.